Literature of the 1950s : good, brave causes - Ferrebe, Alice, 1970- (Edinburgh history of twentieth-century literature in Britain, 2012)
Challenges the myths about apathy and smugness surrounding British literature of the period. Alice Ferrebe's lively study rereads the decade and its literature as crucial in twentieth-century British history for its emergent and increasingly complicated politics of difference, as ideas about identity, authority and belonging were tested and contested. By placing a diverse selection of texts alongside those of the established canon of Movement and 'Angry' writing, a literary culture of true diversity and depth is brought into view. The volume characterises the 1950s as a time of confrontation w.